Relationship between number of crashes and the factors in the environment of urban signalised intersections - Nurul Farhana, Nasarrudin (2018)
Road traffic crash at signalised intersection had becoming one of the main contributors to the increasing number of road traffic crashes in Malaysia. The number of crashes at urban signalised intersection has also recorded a drastic increase for the past ten years and it contributed to the increment in overall number of crashes. Road environment factor appear as most popular factor listed in the road maintenance department’s procedure in improving the signalised intersection in the urban area. In light of that, this study aimed to establish the relationship between number of road traffic crashes and the factors in environment of urban signalised intersection based on the data collected in Kuantan town. In order to model the relationship, 14 intersection environment factors at signalised intersection into account which were the traffic volume, type of land use within 100 m radius from intersection area, number of lanes, approaching speed, width of lane, presence of left-turn channel, presence of median, presence of bus stop, presence of digital traffic signal, width of road shoulder, type of shoulder, presence of uncontrolled turning lane, width of road median; and condition of signage and road markings. Several statistical methods were carried out to develop the model. Firstly, a correlation analysis was used to determine the correlation between each intersection environment factor and signalised intersection crashes. Then, a hypothesis testing was done to determine any possible relationship between intersection environment factors and number of crashes at risky signalised intersection. Lastly, a stepwise regression was used to develop the best relationship model between the intersection environment factors and number of road traffic crashes for signalised intersection in Kuantan Town. The correlation analysis revealed that traffic volume, type of land use within 100 m radius from intersection area, number of lanes, approaching speed, width of lane, presence of left-turn channel, presence of median and width of road median had positive correlation with number of road traffic crashes at urban signalised intersection. Meanwhile, presence of digital traffic signal, width of road shoulder, type of shoulder, presence of uncontrolled turning lane and; condition of signage and road marking has a negative correlation against number of road traffic crashes at urban signalised intersection. Suprisingly, the presence of bus stop had no effect on the number of road traffic crashes at signalised intersection. Results from the hypothesis testing revealed that traffic volume, type of land use within 100 m radius from intersection area, approaching speed, width of lane, presence of uncontrolled turning lane and; condition of signage and road marking were found to be significant in describing the relationship between intersection environment factors and number of crashes at signalised intersection. Main outcome from stepwise regression revealed that developed area, higher approaching speed, poor condition of signage and road marking and; absence of digital traffic signal have significantly contributed to an increase in number of crashes at urban signalised intersection. The outcome from the model is very useful especially for the road improvement team in selecting specific signalised intersection’s element that requires urgent modification. Hence, the signalised intersection’s environment could be control and maintain as to provide safer environment for all road users and consequently, road traffic crashes at signalised intersection also can be reduced.